A review on fermentative hydrogen production from dairy industry wastewater - Karadag, Dogan; Koroglu, Oguz Emre; Ozkaya, Bestami; Cakmakci, Mehmet; Heaven, Sonia; Banks, Charles (WILEY, 2014)
Hydrogen (H-2) is one of the most promising alternative fuel sources for satisfying future energy demand, and fermentative hydrogen production is advantageous over other processes. In recent decades, considerable research has been conducted on H-2 production from carbohydrate-rich materials since it is a cost-effective approach and has the ability to generate intensive renewable energy from organic wastes. Dairy wastewater is a high volume industrial wastewater and with its immense carbohydrate content is an attractive candidate for sustainable fermentative H-2 production. The present paper provides comprehensive evaluation of recent reports on fermentative H-2 production fromdairywastewater. Important effective parameters and current bioreactor technologies for H-2 production from dairy wastewater are discussed. (C) 2014 Society of Chemical Industry
Keywords: fermentative hydrogen; dairy wastewater; bioreactor; two-stage; CONTINUOUS BIOHYDROGEN PRODUCTION; ETHANOL-TYPE FERMENTATION; PACKED-BED REACTOR; CHEESE-WHEY; FOOD WASTE; MICROBIAL COMMUNITY; DARK FERMENTATION; PROCESSING WASTE; CO-DIGESTION; ANAEROBIC FERMENTATION; Biotechnology & Applied Microbiology; Chemistry; Engineering